ANTIMICROBIAL ACTIVITY OF ACTINOMYCETES ISOLATED FROM THE WESTERN GHATS OF TAMILNADU - SIVA KUMAR J,; SANTHANAM, P,; MASILAMANI SELVAM, M, (International Journal of Pharma and Bio Sciences, 2011)
A total of fifty two actinomycetes strains were isolated from the rhizosphere soil of medicinal plants collected from Southeastern Western ghats of Tamilnadu. They were assessed for their antibacterial activity against six human pathogenic bacteria by cross streak method. Out of 52 isolates, five strains were showed high antibacterial activity against all the tested pathogens. Highly active strain (STREP 37) was analyzed further for its morphological and biochemical characteristics for identification. Fermentation conditions were also standardized for the optimum production of antibacterial compounds.